Pengembangan E-Modul Berbasis Kontekstual pada Materi Larutan Elektrolit dan Non Elektrolit untuk Meningkatkan Minat Belajar Siswa: Penelitian - Nurzila Rohmah; M Rusdi; Haryanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research is a development research using the ADDIE development model. The research instruments used are interview sheets and questionnaires. The data analysis techniques used are qualitative and quantitative data. This study aims to determine the development process, feasibility according to experts and media, assessments of chemistry educators and responses and student interest in contextual-based e-modules on electrolyte and non-electrolyte solution materials to improve student learning interest that was developed. The results of this study are that contextual-based e-modules on electrolyte and non-electrolyte solution materials to improve student learning interest received expert feasibility results of 92% (very feasible), media experts of 90% (very feasible), educator assessments of 90% (very feasible), small group trials of 84.8% (very good), and student learning interest of 90.6% (very good). Based on the results of the study, it can be concluded that contextual-based e-modules on electrolyte and non-electrolyte solution materials to improve student learning interest that were developed are feasible to be used as teaching materials in chemistry learning.